2022
DOI: 10.3390/ijerph192013217
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive and Phenomenological Exploration of the Spiritual Needs of Chinese Children Hospitalized with Cancer

Abstract: Spiritual well-being is the fourth dimension of health, as equally important as physical, mental, and social well-being. The shadow of death associated with cancer triggers children to explore their personal values, meanings, and life goals throughout the illness trajectory, enabling them to identify their unique spiritual needs. Chinese children are generally non-religious, unlike Western children, which affects their spiritual needs. To address the literature gaps, we applied a qualitative, descriptive, phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…The results from our previous qualitative study indicated that there were three ways adopted by Chinese childhood cancer patients to establish the connection with others. The three ways included expressing their suffering and emotional distress to their loved ones, feeling of being supported by others, and being helpful to others ( Liu et al, 2022 ). Expressing suffering to their loved ones help them to share and manage their losses, concerns and feelings, thus alleviating their spiritual suffering ( Petersen, 2014 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results from our previous qualitative study indicated that there were three ways adopted by Chinese childhood cancer patients to establish the connection with others. The three ways included expressing their suffering and emotional distress to their loved ones, feeling of being supported by others, and being helpful to others ( Liu et al, 2022 ). Expressing suffering to their loved ones help them to share and manage their losses, concerns and feelings, thus alleviating their spiritual suffering ( Petersen, 2014 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The three ways included expressing their suffering and emotional distress to their loved ones, feeling of being supported by others, and being helpful to others ( Liu et al, 2022 ). Expressing suffering to their loved ones help them to share and manage their losses, concerns and feelings, thus alleviating their spiritual suffering ( Petersen, 2014 ; Liu et al, 2022 ). Feeling of being supported by others can serve as a spiritual support to motivate them to continue the treatment, notwithstanding the suffering caused by cancer ( Petersen, 2014 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations